Effects of Receiving Unlawful Educational Help on the Self-Evaluation of Its Recipient: Can the Unlawful Help Harm Students or Can It Be Beneficial for Them? - Śniecińska, Justyna; Lachowicz-Tabaczek, Kinga (INSTED: Interdisciplinary Studies in Education & Society, 2014)
It is a common belief that unlawful help brings, at least in the short run, only profits to people who use it. Such observations can be supported by research results which suggest that educational cheating is not related with lower evaluation of self-morality. However, there are theories indicating that the help coming from someone similar, i.e. from a peer, independent of whether it is allowed or not, may have a negative impact on its recipient, particularly in the area of self-evaluation connected with a task. According to such an interpretation the unlawful help from a peer should negatively influence the people who use it, because it will lead to changes in self-perception. In order to verify these assumptions a test was carried out, where two groups imagined themselves help and then it was checked how this image influenced their self-picture. In the experimental group the image concerned unlawful help received from a peer, however, in the control group ? the help was allowed and came from a teacher. In accordance with expectations, the unlawful help turned out to negatively influence the self-evaluation and, opposite to expectations ? it also decreased the evaluation of self-morality of its recipients.